Hearing Loss in the Elderly: Is the Hearing Handicap Inventory for the Elderly - Screening Version Effective in Diagnosis When Compared to the Audiometric Test? - Servidoni, Alexandre Barbosa; Conterno, Lucieni de Oliveira (International Archives of Otorhinolaryngology, 2018)
Introduction Hearing losses inherent to the natural process of aging represent today a major public health issue, despite the little attention that their adequate care still receives. Early recognition and proper management of these shortcomings can significantly improve hearing, as well as the patient's general quality of life, reducing the overall impact of this important and prevalent condition of the aging process.Objective The aim of this research was to evaluate the accuracy of the Hearing Handicap Inventory for the Elderly - Screening Version (HHIE-S) in the diagnosis of hearing loss in the elderly when compared with the audiometric test.Methods Through a cross-sectional study, our target population was composed of 138 individuals, aged over 60 and with any otorhinolaryngological complaints, recruited at the Clinic of Otorhinolaryngology and Speech Therapy of the Faculdade de Medicina de Marília (Famema), in the city of Marília, SP, Brazil. Patients already in the process of auditory rehabilitation were excluded, as well as those who did not demonstrate the minimum level of oral understanding necessary to allow the interview.Results The prevalence of hearing loss according to the questionnaire was of 76.1%, while audiometry showed 79.7%. We found the diagnostic accuracy of the instrument to be of 86.2%, with a sensitivity of 89.1% and a specificity of 75.0%, regardless of gender.Conclusion Thereby, we conclude that the standardized questionnaire under rating is suitable for the screening of hearing loss in the elderly, given its high accuracy and user-friendly quality.
Keywords: hearing loss; presbycusis; surveys and questionnaires; audiometry; aged; aging